Rewolucja irańska (1978 – 1979) – przebieg, percepcja, znaczenie - Pietrzykowski, Szymon (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The aim of the article is to characterize the so-called Iranian Islamic Revolution in 1978 – 1979. First part of this paper concerns in ascertaining the chronology of the Revolution (its genesis, decline, watershed moments), the second part in distinguishing three ways of its recognition (the secular, Cold War and religious-cultural narration) in order to emphasize the differences of opinion between various groups or individuals, who took part in the Revolution. Iranian Islamic Revolution was in many ways extraordinary: unlike most revolutions in the twentieth century, which turn progressive, the Iranian one was conservative and resulted in creation of the Islamic Republic of Iran – new particular state with political system based on Shia Islam. However, Iranian Revolution did repeat the fate of its predecessors (violence, dictatorship, social discontent). After over 30 years since the beginning of the Revolution there is an ongoing discussion about its achievements and reasonableness.